2015
DOI: 10.1007/s10877-015-9744-1
|View full text |Cite
|
Sign up to set email alerts
|

Continuous noninvasive cardiac output determination using the CNAP system: evaluation of a cardiac output algorithm for the analysis of volume clamp method-derived pulse contour

Abstract: The CNAP system (CNSystems Medizintechnik AG, Graz, Austria) provides noninvasive continuous arterial pressure measurements by using the volume clamp method. Recently, an algorithm for the determination of cardiac output by pulse contour analysis of the arterial waveform recorded with the CNAP system became available. We evaluated the agreement of the continuous noninvasive cardiac output (CNCO) measurements by CNAP in comparison with cardiac output measurements invasively obtained using transpulmonary thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 28 publications
1
31
2
Order By: Relevance
“…CNAP ® /VERIFY ® : this uses the same technique of photoplethysmography but corrects for changes in vasomotor activity with a specific algorithm; although a high percentage of error has been reported, this is markedly lower when using precalibration with the thermodilution technique 28 . Further validation is needed.…”
Section: Methods Of Hemodynamic Monitoringmentioning
confidence: 99%
“…CNAP ® /VERIFY ® : this uses the same technique of photoplethysmography but corrects for changes in vasomotor activity with a specific algorithm; although a high percentage of error has been reported, this is markedly lower when using precalibration with the thermodilution technique 28 . Further validation is needed.…”
Section: Methods Of Hemodynamic Monitoringmentioning
confidence: 99%
“…40 A similar technology is used in the CNAP monitor (CNSystems Medizintechnik AG, Graz, Austria), which also has shown acceptable agreement with reference CO obtained using TPTD. 41 In a systematic review of noninvasive CO monitoring devices, the noninvasive PCA showed a pooled percentage error of 45%. 42 Other noninvasive CO monitors that are not based on PCA include bioreactance and bioimpedance, 43 partial CO 2rebreathing, 44 and pulse wave transit time.…”
Section: Transition To Minimally Invasive and Noninvasive Hemodynamicmentioning
confidence: 99%
“…As for fluid responsiveness prediction, PPV and SVV analysis from a Nexfin monitor have proven to generate reliable data in patients during mechanical ventilation in non-thoracic surgery or after CABG [78]. Stens et al showed there is some age bias between SVV and PPV: SVV appears more sensitive in younger patients (age < 55 years), while PPV appears more sensitive in older patients (age > 55 years) [79]. Because haemodynamic parameters are derived from a finger or radial artery pulse pressure waveform, significant peripheral vessel resistance changes (such as with oedema or during vasoconstriction using vasoactive drugs), or hand or finger movement [75][76][77] may limit its clinical use.…”
Section: Volume Clamp and Radial Artery Applanation Tonometrymentioning
confidence: 99%